Routledge handbook of neuroscience and the built environment / edited by Alexandros A. Lavdas, Ann Sussman and A. Vernon Woodworth. - Lavdas, Alexandros A.; Sussman, Ann; Woodworth, A. Vernon (Routledge international handbooks., 2026)
According to the OECD (Organization for Economic Cooperation and Development), in the 21st century, we are living in a New Age of Biology, acknowledging the rapid development of transformative findings in the life sciences. This handbook shows how these new findings impact architecture, planning and design, changing our understanding of how people respond to their surroundings, and how they can be optimized for our wellbeing.